(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The investigation of the interrelationships between individuals, place, and condition, and how these differ spatially and transiently crosswise over and between areas, Whereas physical geography focuses on spatial and ecological procedures that shape the normal world and tends to draw on the common and physical sciences for its logical underpinnings and techniques for examination, human geology focuses on the spatial association and procedures forming the lives and exercises of individuals, and their collaborations with spots and nature. Human geology is more aligned with the sociologies and humanities, sharing their philosophical methodologies and techniques (see physical geography for a talk on the connection amongst human and physical geography natural geography.